Impact of Nonclinical Factors on Treatment Decisions: What Can and Cannot Be Done and Why? - Sweney, Matthew T. (Journal of Pediatric Epilepsy, 2020)
This clinical scenario describes a situation where drug-resistant focal epilepsy could have been treated with specific surgery, but a mixture of nonclinical factors led to a different management. The epilepsy started at the age of 6 years and the assessment for other treatment options by this team was done at the age of 12 years. Financial factors were important in the decisions that had to be made and effectively perhaps decisive.
Keywords: drug-resistant focal epilepsy; ethics; seizure burden